ESG AND INTELLECTUAL CAPITAL EFFICIENCY: EVIDENCE FROM ASEAN EMERGING MARKETS - Karyani, Etikah; Perdiansyah, Muhamad Resa (UI Scholars Hub, 2022)
This study aims to investigate the impacts of Environmental, Social, and Governance (ESG) in total and individual performance (“E”, “S”, and “G”) on firms’ intellectual capital (IC) efficiency. The Value-Added Intellectual Coefficient (VAIC) and Modified Value-Added Intellectual Coefficient (MVAIC) were used to measure IC efficiency. Meanwhile, the annual ESG index data from the ASEAN-4 were used to measure ESG from 2015 to 2020. The results show “E”, “S”, and “G” and total ESG positively affect firms’ efficiency in managing IC. In addition, the industry type moderates these relationships in terms of that banks have a greater influence than non-banks. Our results are robust, indicating consistent results. This paper contributes to the literature by examining whether ESG is a determinant of non-financial performance; as far as our observation and knowledge, it is still very limited.